A green templated and nitrogen-incorporated SAPO-34 catalyst for enhanced MTO performance - Mohammad Javad Emami; Jafar Towfighi Darian; Masoud Safari Yazd (Current Research in Green and Sustainable Chemistry)
This study presents a nitrogen-modified SAPO-34 catalyst (SPG), synthesized via a green templated method using coffee powder, to improve the efficiency and stability of the methanol-to-olefins (MTO) process. Compared to conventional SAPO-34 (SP), SPG demonstrates enhanced selectivity, stability, and longevity. Characterization shows a smaller crystallite size (38 nm vs. 46 nm), increased nitrogen incorporation, and well-distributed active sites, improving catalytic activity. Optimized acidity in SPG enhances methanol conversion while reducing coke formation. MD simulations reveal that nitrogen modification improves methanol retention and adsorption energy, promoting ethylene production. Performance tests show SPG achieving 92.6 % light olefin selectivity for 360 min, outperforming SP. Additionally, SPG exhibits superior hydrothermal stability and reduced coke deposition, making it a promising eco-friendly and cost-effective catalyst for industrial MTO applications.